2008
DOI: 10.1002/mrm.21776
|View full text |Cite
|
Sign up to set email alerts
|

Influence of RF spoiling on the stability and accuracy of T1 mapping based on spoiled FLASH with varying flip angles

Abstract: There is increasing interest in quantitative T 1 mapping techniques for a variety of applications. Several methods for T 1 quantification have been described. The acquisition of two spoiled gradient-echo data sets with different flip angles allows for the calculation of T 1 maps with a high spatial resolution and a relatively short experimental duration. However, the method requires complete spoiling of transverse magnetization. To achieve this goal, RF spoiling has to be applied. In this work it is investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
258
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(279 citation statements)
references
References 43 publications
12
258
1
Order By: Relevance
“…Due to its time efficiency, AFI is useful for correction of errors caused by B 1 nonuniformities in quantitative in vivo imaging applications, and particularly, in VFA T 1 mapping (4,(13)(14)(15). Incomplete spoiling in AFI also was identified as a cause of B 1 measurement errors, and the use of diffusion-based gradient spoiling was shown to improve accuracy of this method (16,17).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Due to its time efficiency, AFI is useful for correction of errors caused by B 1 nonuniformities in quantitative in vivo imaging applications, and particularly, in VFA T 1 mapping (4,(13)(14)(15). Incomplete spoiling in AFI also was identified as a cause of B 1 measurement errors, and the use of diffusion-based gradient spoiling was shown to improve accuracy of this method (16,17).…”
mentioning
confidence: 99%
“…Technically, RF spoiling is achieved by linearly incrementing the phase of an RF pulse between successive TR with a specific value of the phase increment. After the initial publication (1) suggested optimal phase increments of 117 or 123 , several other values were proposed (2)(3)(4). Default settings of the RF phase increment also vary between MRI equipment manufacturers (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To address this, we simulated the FLASH acquisitions using Bloch‐Torrey equations for a range of expected transmit field efficiency. The correction parameters describing the linear dependence of the actual T 1 value on the apparent T 1 were derived from these simulations as described in Reference 23 and used to correct for imperfect spoiling of transverse magnetization. Semi‐quantitative maps of the percentage loss of magnetization resulting from the pre‐pulse in the MT‐weighted acquisition were calculated as described by Helms et al17 accounting for spatially varying T 1 times and flip angle inhomogeneities 1…”
Section: Methodsmentioning
confidence: 99%
“…In particular, VFA is more sensitive to variations in excitation flip angle, whereas IR T1 mapping rely on robust inversion efficiency. However, example, it has been suggested that absolute T1 mapping by the VFA method requires absolute FA calibration [26], correction for RF pulse shape [28], and correction for incomplete RF spoiling [29].…”
Section: In Vivo Experimentsmentioning
confidence: 99%